The stratigraphy and origin of the Tofts ridge in north-western Fenland, eastern England. Issue 2 (April 2018) - Brew, David S.; Evans, Graham
Abstract: The Tofts located in north-western Fenland is a low ridge composed of sandy silt, elevated several metres above the surrounding land. Stratigraphically, the feature is the landward edge of an intertidal-subtidal sand body that stretches east into The Wash. It was the location of a Medieval salt-making industry. The ridge seems to have been initiated after 2100 cal years BP by storm waves and/or wind transporting sediment landward from adjacent intertidal flats. Differential consolidation of peat on its landward side and dumping of sediment onto the surface during salt-making enhanced its morphological expression.